Cytokinin Inhibits a Subset of Diageotropica-Dependent Primary Auxin Responses in Tomato - Coenen, Catharina (American Society of Plant Biologists, 2003)
Many aspects of plant development are regulated by antagonistic interactions between the plant hormones auxin and cytokinin, but the molecular mechanisms of this interaction are not understood. To test whether cytokinin controls plant development through inhibiting an early step in the auxin response pathway, we compared the effects of cytokinin with those of the dgt (diageotropica) mutation, which is known to block rapid auxin reactions of tomato (Lycopersicon esculentum) hypocotyls. Long-term cytokinin treatment of wild-type seedlings phenocopied morphological traits of dgt plants such as stunting of root and shoot growth, reduced elongation of internodes, reduced apical dominance, and reduced leaf size and complexity. Cytokinin treatment also inhibited rapid auxin responses in hypocotyl segments: auxin-stimulated elongation, H(+) secretion, and ethylene synthesis were all inhibited by cytokinin in wild-type hypocotyl segments, and thus mimicked the impaired auxin responsiveness found in dgt hypocotyls. However, cytokinin failed to inhibit auxin-induced LeSAUR gene expression, an auxin response that is affected by the dgt mutation. In addition, cytokinin treatment inhibited the auxin induction of only one of two 1-aminocyclopropane-1-carboxylic acid synthase genes that exhibited impaired auxin inducibility in dgt hypocotyls. Thus, cytokinin inhibited a subset of the auxin responses impaired in dgt hypocotyls, suggesting that cytokinin blocks at least one branch of the DGT-dependent auxin response pathway.